Islamic Economics Answers to a Wide Range of Contemporary Socio-Economic Challenges - Reza Muhammad Rizqi; Hartini (Department of Islamic Economics, Islamic University of Indonesia, 2022)
A long period of development spanning more than a century has resulted in traditional economics becoming a highly developed and complex field of study. Finding solutions to existing socio-economic problems is the focus of this paper. The idea of Islamic economics is the central topic of this article. Because it is based on the teachings of the Qur'an and Hadith, the Islamic economic system has proven to be very successful in overcoming various socio-economic problems during the course of human history. In other words, if Islamic economics is used in the right way and in the right way, then one may anticipate many severe socioeconomic difficulties. In short, Islamic economics offers a solution to the problem of how to improve human life. so that no socio-economic problems will be recognized if Islamic economics is practiced in a proper manner. Therefore, Islamic economics focuses primarily on ideas and efforts to improve the general welfare of society. Consequently, Islamic economics is a solution to problems facing society as a whole.